#TITLE_ALTERNATIVE# - INDAWAN UTOMO - 13614025 , RIDHO
Wing in Surface Effect (WiSE) or Wing in Ground Effect (WiG) craft is an air vehicle flying nearby surface to obtain higher aerodynamic performance, such as lift to drag ratio. The effect exists in between the altitude of less than one wing span from the surface. Based on Indonesia’s development in infrastructure and transportation capability, WiSE craft may become one of supporting vehicle to increase mobility in covering off grid and small islands in Indonesia. Previously, WiSE craft has been developed by the Agency for the Assessment and Application of Technology (BPPT) and Bandung Institute of Technology (ITB), building an eight-seater configuration (WiSE 8 Craft). Even though the project was discontinued, until now WiSE crafts are developed extensively by other countries. Hence, this thesis explores WiSE craft of a 20-seater configuration to become a future study of a bigger WiSE craft. This thesis covers the conceptual design phase that consists of determining the geometry, propulsion used, and components’ configuration. Each of the criteria has to be validated by available data and analysis, e.g. aerodynamic analysis. Furthermore, the comparable data will be generated from similar existing WiSE crafts in order to produce a feasible design. The design follows the guideline of aircraft design’s handbook with modified calculation for its hydrodynamic operation. The design is then expressed in 3D model with software CATIA V5R21. The design shows promising result even though its performance only reaches as high as 15 for its lift to drag ratio. The design fulfilled the DRO created based on similar WiSE crafts. However, structural aspect could not be modeled due to its limitation in conceptual design phase. To improve the design, each assumptions and judgements has to be verified with existing data and available analysis.